The Role of Indonesian Women Ulama Congress (KUPI) in the Search for Gender Equality-Based Islamic Law - Faizah, Nur; Rezy Meidina, Ahmad; Lubabul Chadziq, Achmad; Iqbal, Moch.; Umam, M. Shaiful (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Indonesian Women Ulama Congress (KUPI) is an important milestone in integrating the principles of gender equality into the discourse of Islamic law in Indonesia. This Congress not only reflects women's leadership in religious studies but also offers strategies to respond to the challenges of gender inequality that are often legitimized through the interpretation of Islamic law. This study aims to analyze the role of KUPI in developing gender equality strategies through a contextual methodological approach based on maqāshid al-sharīa. This research is classified as qualitative research with a phenomenological approach. Data were collected through document analysis, participant observation, and in-depth interviews with KUPI figures. The analysis combined a critical perspective on societal patriarchal structures and a hermeneutic approach to interpreting religious texts. The results of the study indicate that there are three strategic approaches that KUPI can fight for in fighting for gender equality, namely: (1) reinterpretation of Islamic law that is inclusive of gender issues; (2) community-based advocacy; and (3) strengthening the ulama network. This study concludes that KUPI plays a key role in building a more just Islamic legal paradigm that is not only rooted in Islamic tradition but also in line with human rights principles